Question

[
a x^{2}+b x+c=0
]
Rust Shudent
[
begin{array}{c}
(x-2)(x-3)=0
x^{2}-5 x+6=0
therefore quad Leftrightarrow quad a=1, quad c text { is wrongly }
end{array}
]
( b=-5 . ) Copried as ( b )
Second Shudut
[
begin{array}{c}
1 x^{2}+b x-b=0
x^{2}-5 x-6=0
end{array}
]
( x^{2}-6 x+1 x-6=0 )
[
(x-6)(x+1)=0
]
[
x=-1, b
]

# 14. Two students while solving a quadratic equation inx, one copied the constant term incor- rectly and got the roots as 3 and 2 . The other copied the constant term and coefficient of x2 as -6 and 1 respectively. The correct roots are 1)3,- 2 2 )-3,2 3) -6, -1 4)6,-1

Solution